Genetic diversity across geographical scales in marine coastal ecosystems: Holothuria arguinensis a model species - Rodrigues, F. (2016)
Coastal lagoons are considered one of the most productive areas of our planet harboring a large variety of habitats. Their transitional character, between terrestrial and marine environments, creates a very particular ecosystem with important variations of its environmental conditions. The organisms that are able to survive on these ecosystems frequently experience strong selective pressures and constrictions to gene flowwith marine populations, which could contribute to genetic divergence among populations inhabiting coastal lagoon and marine environments. Therefore, the main aims of this study are to asses the genetic diversity and population structure of Holothuria arguinensis across geographical ranges, to test the hypothesis of coastal lagoons as hotspots of genetic diversity in the Ria Formosa lagoon, and to determine the role of exporting standing genetic variation from the lagoon to open sea and their implications to recent geographical expansion events. To reach these objectives, we investigate the genetic structure of H. arguinensis using two mitochondrial DNA markers (COI and 16S) at different spatial scales: i) small, inside Ria Formosa coastal lagoon, South Portugal; 2) large, including most of the geographical distribution of this species (South and Western Portuguese coast and Canary islands); these results will allow us to compare the genetic diversity of lagoonal and marine populations of H. arguinensis. On this framework, its recent geographical expansion events, recorded by Rodrigues (2012) and González-Wangüemert and Borrero-Pérez (2012), will be analyzed considering the potential contribution from lagoonal genetic pool. Non-significant genetic structure and high haplotypic diversity were found inside the Ria Formosa coastal lagoon. Both genes were unable to detect significant genetic differentiation among lagoonal and marine localities, suggesting a high rate of gene flow. The results supported our hypotheses that coastal lagoons are not only acting as hotspots of genetic diversity, but also contributing for the genetic variability of the species, working as a source of new haplotypes and enhancing adaptation to the high variable conditions. Different genetic patterns of colonization were found on H. arguinensis, but they must be studied more deeply.